Experimental Demyelination and Axonal Loss Are Reduced in MicroRNA-146a Deficient Mice - Martin, Nellie A.; Molnar, Viktor; Szilagyi, Gabor T.; Elkjaer, Maria L.; Nawrocki, Arkadiusz; Okarmus, Justyna; Wlodarczyk, Agnieszka; Thygesen, Eva K.; Palkovits, Miklos; Gallyas, Ferenc; Larsen, Martin R.; Lassmann, Hans; et al. (Frontiers in Immunology, 2018)
Background: The cuprizone (CPZ) model of multiple sclerosis (MS) was used to identify miRNAs related to in vivo de- and remyelination. We further investigated the role of miR-146a in miR-146a-deficient (KO) mice: this miRNA is differentially expressed in MS lesions and promotes differentiation of oligodendrocyte precursor cells (OPCs) during remyelination, but its role has not been examined during demyelination. Methods: MicroRNAs were examined by Agilent Mouse miRNA Microarray in the corpus callosum during CPZ-induced demyelination and remyelination. Demyelination, axonal loss, changes in number of oligodendrocytes, OPCs, and macrophages/microglia was compared by histology/immunohistochemistry between KO and WT mice. Differential expression of target genes and proteins of miR-146a was analyzed in the transcriptome (4x44K Agilent Whole Mouse Genome Microarray) and proteome (liquid chromatography tandem mass spectrometry) of CPZ-induced de- and remyelination in WT mice. Levels of proinflammatory molecules in the corpus callosum were compared in WT versus KO mice by Meso Scale Discovery multiplex protein analysis. Results: MiR-146a was increasingly upregulated during CPZ-induced de- and remyelination. The absence of miR-146a in KO mice protected against demyelination, axonal loss, body weight loss and atrophy of thymus and spleen. The number of CNP+ oligodendrocytes was increased during demyelination in the miR-146a KO mice, while there was a trend of increased number of NG2+ OPCs in the WT mice. MiR-146a target genes, SNAP25 and SMAD4 were downregulated in the proteome of demyelinating corpus callosum in WT mice. Higher levels of SNAP25 were measured by ELISA in the corpus callosum of miR-146a KO mice, but there was no difference between KO and WT mice during demyelination. Multiplex protein analysis of the corpus callosum lysate revealed upregulated TNF-RI, TNF-RII and CCL2 in the WT mice in contrast to KO mice. The number of Mac3+ and Iba1+ macrophages/microglia was reduced in the demyelinating corpus callosum of the KO mice. Conclusions: During demyelination, absence of miR-146a reduced inflammatory responses, demyelination, axonal loss, the number of infiltrating macrophages, and increased the number of myelinating oligodendrocytes. The number of OPCs was slightly higher in the WT mice during remyelination, indicating a complex role of miR-146a during in vivo de- and remyelination.